Expansion of Polymorphonuclear Myeloid-Derived Suppressor Cells in Patients With Gout - Zhong, Limei; Li, Sitao; Wen, Yi; Zheng, Junhui; Liu, Fengbin; Cao, Donglin; Liu, Yufeng (Frontiers in Immunology, 2020)
Abstract Gout is an inflammatory joint disease caused by monosodium urate (MSU) crystals; however, the mechanism underlying MSU-induced inflammation is unclear. Previous research has suggested that inflammation or cancer can drive the expansion of myeloid-derived suppressor cells (MDSCs). In this study, the role of MDSCs in MSU-induced gout inflammation was evaluated. A total of 28 patients with gout, and 20 healthy controls were recruited for the study. MDSCs, and their functions, were analyzed by flow cytometry and a T cell co-culture assay, respectively. We observed a higher frequency of PMN-MDSCs, and a stronger immunosuppressive function, in patients with gout compared to the controls. Moreover, circulating PMN-MDSCs were positively correlated with pathological indicators, including uric acid and C-reactive protein levels. We also demonstrated that MSU can induce significant PMN-MDSC expansion, using in vivo and in vitro experiments. Finally, MSU-induced PMN-MDSCs produced higher levels of IL-1β, which mediated gout inflammatory progression. Our results demonstrate that MSU modulates the expansion and suppressive function of PMN-MDSCs, providing insights into a novel mechanism underlying the pathogenesis of MSU-induced gout. Thus, MDSCs may be useful for the development of novel therapeutic strategies for the prevention and treatment of gout.